The influence of online opinion leaders on the purchase intention of Chinese university students - Shi, Jiayi (2020)
The aim of this study is to examine the influence of online opinion leaders on the purchase intention of Chinese university students in the context of social media marketing based on the technical acceptance model. A literature review is conducted that focuses on consumer decision-making models and the characteristics of online opinion leaders. To identify the impact of the independent variable on purchase intention (both with and without the existence of other variables), Pearson correlation coefficient analysis and multiple regression analysis are used. The findings suggest that, for online opinion leaders,their interactivity, personality strength, and homogeneity have a positive impact on the purchase intention of Chinese university students through perceived usefulness and perceived ease of use. Moreover, perceived ease of use plays a partly mediating role between perceived usefulness and the characteristics of online opinion leaders; however, this role is not significant. The study concludes by considering the implications for the findings, taking into consideration the specific attributes to Chinese social media marketing.